an Analysis of Idioms Found in Avatar: The Way of Water Movie - Hartati, Risda; Sinambela, Erika; Elfrida, Rotua (LPPPIPublishing, 2024)
This study analyzes the idiomatic expressions found in the movie “Avatar: the Way of Water,” aiming to identify the various types of idioms found and to highlight the most dominant idiomatic expressions found by the characters. The study underscores the importance of idioms in enriching dialogue with emotional depth and authenticity, thereby enhancing the overall narrative experience. The paper outlines its objectives to shed light on how these idiomatic expressions influence character development and audience engagement. Employing a qualitative descriptive approach, the research primarily draws on the moviescript as its data source. In total, 58 idiomatic expressions were identified. 1 simile, 17 clichés, 36 fixed statements, and 4 other languages. Among these, fixed statement found as the most dominant types, comprising 62% of the total instances observed. The findings indicate that idiomatic expressions not only enhance dialogue but also foster an emotional connection between the characters and the audience. Moreover, the study brings to light the difficulties that non-native English speakers face in understanding these expressions, emphasizing the necessity for idiomatic knowledge among language learners. Ultimately, this research enhances our understanding of idiomatic expressions in movie and highlights their crucial role in enhancing narrative and character engagement throughout the story.